Die Künstler aus Gugging - Museum Gugging, Klosterneuburg; Museum Moderner Kunst, Wien; Salzburger Landessammlungen Rupertinum, Salzburg; Kunstamt Wedding, Berlin; Heidelberger Kunstverein, Heidelberg; Neue Galerie der Stadt Linz/Wolfgang-Gurlitt-Museum, Linz (Wien - Berlin : Medusa Verlag, 1983)
Artenjak, Franz ; Artur ; Aurel ; B., Alois ; B., Johann ; Bachler, Josef ; Blahaut, Joseph ; Bleier, Paul ; Dobay, Anton ; Fischbach, Alois ; Fischer, Johann ; Gableck, Franz ; Garber, Johann ; Gittenberger, Johann ; Glanz, Richard Robert ; Hauser, Johann ; Herbeck, Ernst ; Horacek, Rudolf ; Kamlander, Franz ; Kernbeis, Franz ; Koller, Fritz ; Korec, Johann ; L., Rupertus ; Mach, Edmund ; Max ; N., Franz ; Opitz, Fritz ; Prinz, Otto ; Sch., Johann ; Schöpke, Philipp ; Till, Josef ; Tschirtner, Oswald ; Walla, August ; Zittra, Erich
Die Künstler aus Gugging, Ausstellungen: Museum Moderner Kunst, Wien ; Salzburger Landessammlungen Rupertinum ; Kunstamt Wedding, Berlin ; Heidelberger Kunstverein ; Neue Galerie der Stadt Linz Wolfgang-Gurlitt-Museum, 1983
Duits
kunstcatalogus